2008
DOI: 10.4049/jimmunol.180.4.2514
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Prevent Control of Experimental African Trypanosomiasis

Abstract: African trypanosomes are single-cell, extra-cellular blood parasites causing profound immunosuppression. Susceptible BALB/c mice infected s.c. into a footpad with 104 Trypanosoma congolense die with fulminating parasitemia within 10 days. We injected BALB/c mice 2 days before such an infection with different doses of a depleting mAb specific for CD25, a surface marker of regulatory T cells (Tregs). Pretreatment with a low, optimal dose of anti-CD25 resulted in a dramatic effect, in that the infected mice did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
68
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 37 publications
4
68
0
Order By: Relevance
“…Several studies investigated the role of Treg in infections with helminths or other parasites and yielded in diverging conclusions (reviewed in [1] and [13]). There is evidence that certain parasites depend on Treg action for their persistence [14][15][16][17]. Other species profit more indirectly from Treg circuits, which control infectioninduced pathology [18][19][20].…”
mentioning
confidence: 99%
“…Several studies investigated the role of Treg in infections with helminths or other parasites and yielded in diverging conclusions (reviewed in [1] and [13]). There is evidence that certain parasites depend on Treg action for their persistence [14][15][16][17]. Other species profit more indirectly from Treg circuits, which control infectioninduced pathology [18][19][20].…”
mentioning
confidence: 99%
“…Because we and others have previously shown that regulatory T cells (Tregs) prevent the control of infection with T. congolense (24,25), we wondered whether lowdose intradermal infection was associated with expansion of these cells. Therefore, we infected mice intradermally with 10 3 T. congolense parasites and on the indicated days assessed the percentages and absolute numbers of CD4 ϩ CD25 ϩ Foxp3 ϩ regulatory T cells in the spleens and draining lymph nodes by flow cytometry.…”
Section: Primary Low-dose Id T Congolense Infection and Susceptibimentioning
confidence: 99%
“…5A and B). Because previous studies showed that Tregs negatively influence the outcome of T. congolense infection in mice (24,25), we hypothesized that depletion of Tregs during challenge infection will abrogate the enhanced susceptibility mediated by repeated low-dose intradermal infection. We therefore injected mice repeatedly with 10 2 T. congolense parasites (2 times with a 1-week interval), and on the third week injected them with anti-CD25 monoclonal antibody (PC61) to deplete Tregs as we have done previously (25,30).…”
Section: Primary Low-dose Id T Congolense Infection and Susceptibimentioning
confidence: 99%
See 2 more Smart Citations